2015
DOI: 10.1002/smll.201500044
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Galvanic Replacement of Supported and Colloidal Cu2O Nanocrystals with Gold and Palladium

Abstract: Galvanic replacement reactions (GRRs) on nanoparticles (NPs) are typically performed between two metals, i.e., a solid metal NP and a replacing salt solution of a more noble metal. The solution pH in GRRs is commonly considered an irrelevant parameter. Yet, the solution pH plays a major role in GRRs involving metal oxide NPs. Here, Cu(2)O nanocrystals (NCs) are studied as galvanic replacement (GR) precursors, undergoing replacement by gold and palladium, with the resulting nanostructures showing a strong depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
(124 reference statements)
1
20
0
Order By: Relevance
“…The effect of temperature on the formation of the alloy was studied by varying the temperature of the mixture from room temperature to 80 °C.It was observed that the AgAuQC synthesized at 55 °C exhibited the highest emission intensity (Figure E).Hence, the synthesis conditions like the concentration of HAuCl 4 , the reaction temperature and the pH of the medium were optimized as 1 mM, 55 °C and 5–6 pH, respectively. The influence of the solution pH on the mechanism and products in GERs has not been addressed in most of the published works as the acid and base have no influence on the redox potential of metal ions . Thus, GER is considered to be a pH‐independent reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of temperature on the formation of the alloy was studied by varying the temperature of the mixture from room temperature to 80 °C.It was observed that the AgAuQC synthesized at 55 °C exhibited the highest emission intensity (Figure E).Hence, the synthesis conditions like the concentration of HAuCl 4 , the reaction temperature and the pH of the medium were optimized as 1 mM, 55 °C and 5–6 pH, respectively. The influence of the solution pH on the mechanism and products in GERs has not been addressed in most of the published works as the acid and base have no influence on the redox potential of metal ions . Thus, GER is considered to be a pH‐independent reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to promote Au formation on Cu 2 O, the solution should be acidic to force reaction 2 to the right. This is ensured when 5 mM of HAuCl 4 is used for the galvanic replacement process [ 48 ]. Figure 4 shows SEM images of the restructured copper electrode after galvanic replacement with gold using 5 mM HAuCl 4 for 1, 3 and 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used to create many copper based bimetallic electrodes with interesting properties [ 41 , 42 , 43 , 44 ]. However, this work has also been extended to the galvanic replacement of metal oxide surfaces, such as Cu 2 O to create Cu 2 O/M (M = Pt, Pd, Au) materials that have potentially excellent applications [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…As disproportionation is characteristic of the interfacial chemistry between the acidic media and the Cu 2 O surface, it potentially mediates the GR reaction observed for other noble metal salts, such as Ag + , PtCl 6 2À or PdCl 4 2À , which also have appropriate reduction potentials for driving GR reactions on Cu and Cu 2 O. [31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%